2022
DOI: 10.1017/s2045796022000075
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and death by other causes among patients with a severe mental illness: cohort study comparing risks among patients discharged from inpatient carev. those treated in the community

Abstract: Aims People diagnosed with a severe mental illness (SMI) are at elevated risk of dying prematurely compared to the general population. We aimed to understand the additional risk among people with SMI after discharge from inpatient psychiatric care, when many patients experience an acute phase of their illness. Methods In the Clinical Practice Research Datalink (CPRD) GOLD and Aurum datasets, adults aged 18 years and older who were discharged from psychiatric inpatient care in England bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The current study showed similar findings with the results of previous studies 3,7,8,15,16,34–37 . In keeping with past research, 12,24,38 suicide risk peaked during the first 3 months after discharge and increased suicide risk could persist for many years post‐discharge. We also found greater relative risk elevation for suicide in females than males, similar to previous findings that relative risk for suicide increased more markedly in female than male patients with a history of psychiatric admission 38,39 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The current study showed similar findings with the results of previous studies 3,7,8,15,16,34–37 . In keeping with past research, 12,24,38 suicide risk peaked during the first 3 months after discharge and increased suicide risk could persist for many years post‐discharge. We also found greater relative risk elevation for suicide in females than males, similar to previous findings that relative risk for suicide increased more markedly in female than male patients with a history of psychiatric admission 38,39 .…”
Section: Discussionsupporting
confidence: 92%
“…The proportional hazards assumption was assessed by plotting Schoenfeld residuals versus time and examining their correlation; there was evidence for violation of the assumption. Therefore, in line with our aim to examine the mortality trajectories, we estimated HRs for each of the six follow‐up periods to allow a direct comparison of the relative mortality risks across different post‐discharge periods, similar to the approach used in some recent studies on post‐discharge mortality in psychiatric patients 11,12 . Overall and sex‐specific HRs and their 95% confidence intervals (CIs) were estimated in each of the six separate models for different follow‐up periods; each model had different starting and end points of follow‐up.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations